Dampak Pergantian Kurikulum Pendidikan terhadap Peserta Didik Sekolah Dasar - Yuniastuti, Hanifa; Syahrirra, Nessa; Rusma, Siti Mutia; Andriani, Oktavia (TSAQOFAH, 2023)
The foundation of this exploration was that toward the start of changing the educator educational program as teachers they had not had the option to execute the new educational program in general, in a few regions the offices claimed by schools were an impediment to the fruitless execution of the new educational program, and educational program changes surely expected effort to educators who were implementers in the field. The purpose of this study is to find out how changing the educational curriculum affects students in elementary schools. The technique utilized in this study utilizes an expressive strategy. The study found that the educational process was well-conceived in the 2013 curriculum. However, the field implementation did not go as planned. In the meantime, the Independent Curriculum was successfully implemented in a number of Mobilization Schools the first year, and this year, it was expanded to a number of schools. A few schools are as yet planning the right equation for carrying out the Free Educational program. After being analyzed, this description indicates that the implementation of the Independent Curriculum is superior and in line with educational culture. However, policymakers and educators need to keep a few things in mind if they want the Independent Curriculum to work as well as the 2013 Curriculum in elementary education.